1999
DOI: 10.1002/(sici)1099-0690(199907)1999:7<1595::aid-ejoc1595>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Fluorescence Properties, and Head-to-Tail Regioselectivity in the Photodimerization of a Donor–Acceptor-Substituted Anthracene

Abstract: The novel 2,6‐donor–acceptor‐substituted anthracene, namely 6‐methoxy‐2‐anthracene carboxylic acid (7), was synthesized. The emission of this compound exhibits significant solvatochromism. The fluorescence band position and intensity are also remarkably sensitive to H+. Irradiation of the anthracene 7 in solution yields the syn and anti head‐to‐tail dimers exclusively. A synergistic electronic effect between the donor and acceptor substituents is proposed to operate on the photophysical and photochemical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 52 publications
3
19
0
Order By: Relevance
“…[16,32] Nevertheless, there are reports of regioselective head-to-tail dimerizations of other aza-heterocyclic aromatic compounds [33] and of a 2,6-donor ± acceptor-substituted anthracene. [34] The selectivity of the dimerization may be due to the thermal lability of the head-to-head isomers, since 1 H NMR spectroscopy indicated that very small amounts of head-to-head isomers are formed on photolysis, which then smoothly cyclorevert at room temperature. Since these dimers may be detected by NMR spectroscopy, they should be sufficiently long lived to permit their observation.…”
Section: Discussionmentioning
confidence: 99%
“…[16,32] Nevertheless, there are reports of regioselective head-to-tail dimerizations of other aza-heterocyclic aromatic compounds [33] and of a 2,6-donor ± acceptor-substituted anthracene. [34] The selectivity of the dimerization may be due to the thermal lability of the head-to-head isomers, since 1 H NMR spectroscopy indicated that very small amounts of head-to-head isomers are formed on photolysis, which then smoothly cyclorevert at room temperature. Since these dimers may be detected by NMR spectroscopy, they should be sufficiently long lived to permit their observation.…”
Section: Discussionmentioning
confidence: 99%
“…But apart from functionalization at the meso positions (C9, C10) 78,85 the synthesis of such anthracene derivatives, especially with donor and acceptor functionalities in the lateral positions, is a rather elaborate project. [86][87][88][89][90] In contrast, the pyridinium unit within the benzo[b]quinolizinium already constitutes an intrinsic acceptor functionality, so that already the introduction of a single electron donating substituent in a "conjugated" position (i.e. position 2, 4, 6, 7, 9 or 11) establishes a donoracceptor system.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…Antracene and its derivatives are among the most useful polycyclic aromatic compounds [14]. In view of their fluorescent prperties, they are of practic1 interest as chemosensors and markers in supramolecular systems [1 1, 15-17].…”
Section: Fluorescent Chemosensorsmentioning
confidence: 99%